A Biologically Derived Pectoral Fin for Yaw Turn Manoeuvres. Issue 1 (1st March 2010) - Gottlieb, Jonah R.; Tangorra, James L.; Esposito, Christopher J.; Lauder, George V.
Abstract : A bio-robotic fin has been developed that models the pectoral fin of the bluegill sunfish as the fish turned to avoid an obstacle. This work involved biological studies of the sunfish fin, the development of kinematic models of the motions of the fin's rays, CFD based predictions of the 3D forces and flows created by the fin, and the implementation of simplified models of the fin's kinematics and mechanical properties in a physical model. The resulting robotic fin produced the forces and flows that drove the manoeuvre and had a sufficiently high number of degrees of freedom to create a variety of non-biologically derived motions. The results indicate that for robotic fins to produce a level of performance on par with biological fins, both the kinematics and the mechanical properties of the biological fin must be modelled well.